Variety Gains of Trade I ntegration in a Heterogeneous Firm Model - D'Artis Kancs (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
The present paper studies the variety gains of regional integration in Asia. Applying a heterogenous firm model we are able to assess the gains arising from the increased product and consumer choice, which is not possible in trade models with representative firms. We analyse the impacts of the ongoing trade liberalisation in South East Asia in three scenarios: CIFTA, ASEAN+3, and ASEAN+6. We find that the gains from trade integration are substantial, particularly in the multilateral liberalisation scenario ASEAN+6. A multilateral reduction of fixed and variable trade barriers by 15 percent results in a trade growth of 34 percent, which due to the additional extensive margin of trade, is larger than in trade models with representative firms. Similarly, due to the additional gains from variety growth, the welfare gains of trade integration in Asia are up to 9 percent higher than trade models with representative firms would predict.
Keywords: C68; F12; F14; F17; R12; R23; 330; Variety gains; trade integration; Asia; heterogenous firms; Handelsregionalismus; Außenhandelsliberalisierung; Außenhandelseffekt; Räumliche Verteilung; Außenwirtschaftstheorie; Südostasien